Improving CAR skills for Middle School Teachers in Pontianak City - Agus Wartiningsih; Y. Touvan Juni Samodra; Ahadi Sulissusiawan; Agus Syahrani; Parlindungan Nadeak; Melilisa Jupitasari (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The community service is an activity to facilitate junior high school teachers in Pontianak City to improve their skills in conducting Classroom Action Research (CAR). CAR implementation training is essential because, through CAR, teachers can always identify various problems that occur in the learning process. Through PTK, teachers can also provide the best and most appropriate solutions to problems. The method used is the method of exercises, discussions, and assignments within three months, namely October-December. Qualitatively, training for junior high school teachers at junior high schools in Pontianak City can run optimally and produce CAR, which can be implemented in the learning process. Maximum results with 17 finish of 18 participants completing the PTK report. One participant did not finish because he withdrew from the beginning of the process.